Resolving Astrocyte Heterogeneity in the CNS - Farmer, W. Todd; Murai, Keith (Frontiers in Cellular Neuroscience, 2017)
Astrocytes play essential roles in nearly all aspects of brain function from modulating synapses and neurovasculature to preserving appropriate extracellular solute concentrations. To meet the complex needs of the central nervous system, astrocytes possess highly specialized properties that are optimized for their surrounding neural circuitry. Precisely how these diverse astrocytes types are generated in vivo, however, remains poorly understood. Key to this process is a critical balance of intrinsic developmental patterning and context-dependent environmental signaling events that configures astrocyte phenotype. Indeed, emerging lines of evidence indicate that persistent cues from neighboring cells in the mature CNS cooperate with early patterning events to promote astrocyte diversity. Consistent with this, manipulating Sonic hedgehog (Shh), Notch, and fibroblast growth factor (FGF) signaling in the adult brain, have profound effects on the structural, morphological, and physiological state of mature astrocytes. These pathways may become disrupted in various neurological diseases and contribute to CNS pathology. This mini-review focuses on how context-dependent environmental cues cooperate with intrinsic developmental patterning events to control astrocyte diversity in vivo in order to promote healthy brain function.